Multi-level analysis framework for reviewing IDT-based studies - Mahdi Omidi; Qingfei Min; Ali Omidi (Cogent Business & Management, 2017)
Researchers have for years emphasized the value of multi-level studies. This research attempts to develop a framework for analyzing IT adoption studies from a multi-level perspective. Specifically, it examines research involving Innovation Diffusion Theory (IDT), using a framework devised on the multi-level analysis guidelines proposed by two studies. Four empirical IDT-based research papers are reviewed by applying the developed multi-level analysis framework. In doing so, this paper finds that by following the proposed framework, researchers can avoid the weakness of level bias caused by single-level analysis. In addition, the framework provides insights for managerial strategies in successful information system implementation, adoption and diffusion. Finally, the proposed framework can be referenced by future researchers for conducting multi-level analysis on IT adoption-related topics.
Keywords: 650